Isoallopregnanolone reduces tic‐like behaviours in the D1CT‐7 mouse model of Tourette syndrome - Cadeddu, Roberto; Bäckström, Torbjörn; Floris, Gabriele; Nordkild, Peter; Segerdahl, Märta; Bortolato, Marco (Journal of neuroendocrinology, 2020)
Tourette syndrome (TS) is a neuropsychiatric disorder characterised by multiple, persistent tics. These semi‐voluntary motor and phonic manifestations are typically aggravated by exposure to acute stress, yet the mechanisms underlying this exacerbation remain unclear. Using a well‐characterised animal model of TS, the D1CT‐7 mouse, we recently showed that acute stress increases tic‐like responses and causes sensorimotor gating deficits, as measured by the prepulse inhibition of the startle. We showed that these effects are promoted by the brain synthesis of the neurosteroid allopregnanolone (AP). In line with this idea, inhibition of AP synthesis by finasteride was found to suppress the tic‐exacerbating effects of stress; conversely, AP administration resulted in a marked enhancement of the number of tic‐like motor bursts. Given that the primary mechanism of AP is based on the positive allosteric modulation of GABAA receptors, in the present study, we hypothesised that the enhancement in tic‐like behaviours induced by either stress or AP may be countered by isoallopregnanolone (isoAP), the natural 3β‐epimer of AP that acts as an antagonist to the AP‐binding site within GABAA receptors. In agreement with our hypothesis, isoAP (5‐10 mg kg‐1, s.c.) dose‐dependently reduced the number of tic‐like behaviours induced by stress in D1CT‐7 mice. These effects were comparable to those elicited by both the benchmark TS therapy haloperidol (0.3 mg kg‐1, i.p.), as well as finasteride (25 mg kg‐1, i.p.). IsoAP also countered the prepulse inhibition deficits secondary to stress in D1CT‐7 mice. Finally, isoAP opposed the enhancement of tic‐like behaviours induced by AP (15 mg kg‐1, i.p.). Given that isoAP is well‐tolerated and has an optimal safety profile, these data suggest that this steroid may have therapeutic properties in TS.